An empirical evaluation of "marking menus" - Kurtenbach, Gordon P.; Sellen, Abigail; Buxton, Bill (Human-Computer Interaction, 1993)
We describe "marking menus", an extension of "pie menus" which makes . Pie menus are circular menus subdivided into sectors, each of which might correspond to a different command. Marking menus are pie menus in which the path of the cursor leaves an ink trail. Thus, selecting a sector from a marking menu creates a visual mark similar to a pen stroke on paper. Marking menus are also unique in that they ease the transition from novice to expert user. Novices can “pop-up” a menu and make a selection, whereas experts can simply make the corresponding mark without waiting for the menu to appear. This paper describes an experiment designed to explore both articulatory and cognitive aspects of pie and marking menus. "Articulatory aspects" refers to how well subjects could execute the physical actions necessary to select from pie menus, given three different kinds of input devices (mouse, trackball, and stylus), and as the number of items in the menu increases. Articulatory aspects were investigated by presenting one group of subjects with the task of selecting from fully visible or "exposed" menus. To investigate the cognitive aspects, two other groups of subjects used invisible or "hidden" pie menus: one group with an ink trail, and one without. In order for marking menus to work effectively, users must be able to mentally represent and associate Selection from hidden menus was designed to reveal Both number of slices per menu and input device were systematically varied. We discuss the findings with respect to menu size, input device, analysis of markings used, and learning.